“My Eucharist to the people of District 11”: bread, sacrifice and thanksgiving in The Hunger Games - Bloomfield, Jem (SAGE Publications, 2017)
The imagery of bread in The Hunger Games provides an opportunity to read the novel within a Christian tradition alert to themes of suffering, sacrifice and solidarity. This article examines how the novel “re-enchants” bread as both a site of ideological conflict and potential social healing, and draws out how this relates to the book’s place within consumer capitalism and Young Adult fiction. It also considers how a Christian interpretation might connect to current tensions around inclusion and identity.